A formação para a cidadania em discursos de professores de física - ALENCAR, José Ricardo da Silva (Universidade Federal do Pará, 2011)
We investigate the speech of physics teachers about the citizen formation. This formation has been become as an important Educational Goals for the last years. The Educational Laws and Parameters and the Researches in Scientific Education have been focused to the formation of citizens. Such characteristics are in the school speech and they are influencing the protagonists of the educative practices. Thus, we investigate on teachers' conceptions and proposals about the Formation for the Citizenship. We reflect on its ideas over teaching physic focused to scientific literacy for all citizens, thus, we bring as subject in this investigation the speeches of professors of Physics. So, we choose three teachers' Physics with criteria that they are concerned with the innovation of this discipline. Thus, such teachers had been interviewed and, from their speeches, we use as methodology the Qualitative Analysis of Text. We use this methodology which took us to the debate of aspects as the conceptualizations that the teachers have about citizenship, the relationship they infer between the teaching Physics and the scientific literacy, as well as of factors that influence or could influence for a transformation in the way to conceive a Scientific Literacy. So, we can infer: the Physics is conceived by the teachers as an important factor in the life of a citizen: they believes that there is an intense relationship between the contextualized scientific knowledge and the formation of critical sense of the citizen and express positions that are scientifically and technologically informed; there is an approach between the speeches of these teachers and the one in the Education Documents and new Parameters in Scientific Education; the inefficacy of initial formation of these teachers for teaching practices what makes impracticable proposals and alternative strategies to the citizen formation. Thus, based in our analysis, the results of this research in takes us to infer that for an effective implementation of the Scientific Education focusing scientific literacy in high schools, a turn point, by the professors, must be did: the rupture with Traditional Education and a epistemological and pedagogical turning of the Physical Education. Moreover, to include in teaching physics the formation for praxis citizen based in scientific and ethical knowledge, as well as the daily citizen practice of express opinions and action in society.